Inflation and the UK Labour Market. - Nickell, S (1990)
This paper explores the reasons why inflation is, and has been for four decades, endemic in Britain. We argue that there is a fundamental supply-side constraint in the economy which takes deficit and increases in inflation. The mix of monetary and fiscal policy, along with private sector demand shocks, determines which combination of these three outcomes then occurs. In Britain, the fundamental constraint has shifted adversely over the last two decades and we enumerate some of the factors underlying this shift. As a consequence, policy makers have been confronted with ever more difficult choices and this has resulted in a persistent problem of high unemployment and relatively high inflation.